ASSESSMENT OF THE SOCIO-ECONOMIC TRANSFORMATION OF ENTREPRENEURSHIP IN THE CONTEXT OF THE DIGITALIZATION OF THE ECONOMY: SCIENTIFIC AND PRACTICAL ASPECTS (Development Service Industry Management, 2025)
The article examines the socio-economic transformation of entrepreneurship in the context of economic digitalization, emphasizing its multidimensional impact on business activity, labor markets, and institutional development. It is substantiated that digitalization acts as a key driver of structural changes in entrepreneurship, transforming traditional business models, employment patterns, competency requirements, and mechanisms of value creation. The study highlights that digital transformation generates not only economic outcomes but also significant social effects, including changes in social adaptation, the emergence of digital inequality, and the growth of new risks for business entities.The paper analyzes contemporary scientific approaches to assessing the impact of digitalization on entrepreneurial activity, including the substitution theory approach, the socio-economic approach, the institutional and digital risk assessment approach, and the competency-based approach. Their strengths and limitations are identified, demonstrating that existing methodologies remain fragmented and insufficient for capturing the complex interrelation between economic performance and social effects of digital transformation.Based on the synthesis of theoretical and methodological foundations, an integrated multilevel model for assessing the socio-economic transformation of entrepreneurship is proposed. The model encompasses macro-, meso-, and micro-levels, enabling a comprehensive evaluation of digital transformation processes and their outcomes. It combines quantitative and qualitative indicators to identify causal relationships between digitalization and business performance, as well as the integration of entrepreneurship into global markets. The proposed model provides a methodological framework for evidence-based managerial decision-making and public policy development aimed at fostering digital entrepreneurship and enhancing economic competitiveness. The findings contribute to the advancement of scientific approaches to evaluating digital transformation by offering a systematic and holistic assessment tool applicable to enterprises of different scales and sectors.
Keywords: digitalization; economy; entrepreneurial activity; innovation and information economy; socio-economic transformation; substitution theory; digital technologies; human capital; risks; multilevel model